IMF Staff Papers, Volume 50, Special Issue, IMF Third Annual Research Conference - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2003)
The paper discusses a model in which growth is a negative function of fiscal burden. Moreover, growth discontinuously switches from high to low as the fiscal burden reaches a critical level. The paper provides an overview of key elements of corporate bankruptcy codes and practice around the world that are relevant to the debate on sovereign debt restructuring. It also describes the broad trends in international financial integration for a sample of industrial countries and explains the cross-country and time-series variation in the size of international balance sheets.